2014
DOI: 10.1111/cup.12364
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the VE1 immunostain for the BRAFV600E mutation in melanoma

Abstract: BACKGROUND BRAF mutation status, and therefore eligibility for BRAF inhibitors, is currently determined by sequencing methods. We assessed the validity of VE1, a monoclonal antibody against the BRAF V600E mutant protein, in the detection of mutant BRAF V600E melanomas as classified by DNA pyrosequencing. METHODS The cases were 76 metastatic melanoma patients with only one known primary melanoma who had had BRAF codon 600 pyrosequencing of either their primary (n=19), metastatic (n=57) melanoma, or both (n=17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 31 publications
4
48
0
Order By: Relevance
“…Heterogeneous BRAF V600E IHC expression has been reported in 2.6% to 35% of melanoma tumor samples tested [9, 10, 14, 22, 23]. Here, we also confirm heterogeneous BRAF V600E IHC expression pattern in a subset of melanomas.…”
Section: Discussionsupporting
confidence: 85%
“…Heterogeneous BRAF V600E IHC expression has been reported in 2.6% to 35% of melanoma tumor samples tested [9, 10, 14, 22, 23]. Here, we also confirm heterogeneous BRAF V600E IHC expression pattern in a subset of melanomas.…”
Section: Discussionsupporting
confidence: 85%
“…22 In the current study, intratumoral heterogeneity was seen only in one case, whereas intertumoral heterogeneity in the same patient (comparison of immunohistochemistry for NRAS mutational status of primary vs paired metastatic samples) was not an aim of the current study and future investigations will assess concordance of NRAS protein expression in multiple patient's tumors. Previous immunohistochemical analyses using BRAFV600E antibody have shown that intratumoral heterogeneity of BRAF mutation is not generally observed [23][24][25] and up to 100% concordance between matched primary and metastatic melanomas has been reported. 24 These results support the routine use of immunohistochemistry with the anti-BRAFV600E antibody as an ancillary screening tool to assess the BRAFV600E mutation status in melanoma patients 26 for treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…Previous immunohistochemical analyses using BRAFV600E antibody have shown that intratumoral heterogeneity of BRAF mutation is not generally observed [23][24][25] and up to 100% concordance between matched primary and metastatic melanomas has been reported. 24 These results support the routine use of immunohistochemistry with the anti-BRAFV600E antibody as an ancillary screening tool to assess the BRAFV600E mutation status in melanoma patients 26 for treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical staining was performed in the UNC Department of Dermatology Dermatopathology Laboratory as we have recently described (23). Briefly, freshly cut 4-μm thick sections of formalin-fixed and paraffin-embedded melanoma tissue blocks were stained using the fully automated Leica Bond III system.…”
Section: Methodsmentioning
confidence: 99%